Asymmetric Deoxygenative Alkynylation of Tertiary Amides Enabled by Iridium/Copper Bimetallic Relay Catalysis - Li, Zhaokun; Zhao, Feng; Ou, Wei; Huang, Pei‐Qiang; Wang, Xiaoming (Angewandte Chemie International Edition, 2021)
A variety of inert tertiary amides have been successfully transformed into synthetically important chiral propargylamines in high yields with good to excellent enantioselectivities via a relayed sequence of Ir catalyzed partial reduction and Cu/GARPHOS catalyzed asymmetric alkynylation with terminal alkynes. The reaction was readily extended to some drug molecules and the transformations of representative products have been demonstrated, thus attesting the practical utilities and the robust nature of the protocol. An Ir/Cu bimetallic relay catalysis was developed to achieve the challenging asymmetric deoxygenative alkynylation of inert amides under mild conditions, affording a series of synthetically important chiral propargylamines in high yields with good to excellent enantioselectivities.